2014
DOI: 10.1371/journal.pone.0096712
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Expression and Characterization of the Cytoplasmic Rice β-Glucosidase Os1BGlu4

Abstract: The Os1BGlu4 β-glucosidase is the only glycoside hydrolase family 1 member in rice that is predicted to be localized in the cytoplasm. To characterize the biochemical function of rice Os1BGlu4, the Os1bglu4 cDNA was cloned and used to express a thioredoxin fusion protein in Escherichia coli. After removal of the tag, the purified recombinant Os1BGlu4 (rOs1BGlu4) exhibited an optimum pH of 6.5, which is consistent with Os1BGlu4's cytoplasmic localization. Fluorescence microscopy of maize protoplasts and tobacco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…A highly significant SNP (no. 53) on chromosome 8 lies in gene ZmBLGU42 (Zm00001d012159; Figure 7A) which putatively encodes for a b-glucosidase orthologous to rice Os1bglu4 (Rouyi et al, 2014). We found that, compared with PHG35, transcript levels of ZmBLGU42 were higher in B73 at 33, 39, and 42 DAA but identical in both inbred lines at 36 DAA ( Figure 7B).…”
Section: Functional Validation Of Candidate Genesmentioning
confidence: 87%
See 1 more Smart Citation
“…A highly significant SNP (no. 53) on chromosome 8 lies in gene ZmBLGU42 (Zm00001d012159; Figure 7A) which putatively encodes for a b-glucosidase orthologous to rice Os1bglu4 (Rouyi et al, 2014). We found that, compared with PHG35, transcript levels of ZmBLGU42 were higher in B73 at 33, 39, and 42 DAA but identical in both inbred lines at 36 DAA ( Figure 7B).…”
Section: Functional Validation Of Candidate Genesmentioning
confidence: 87%
“…Key insights into the role of ZmBLGU42, a b-glucosidase orthologous to Arabidopsis BGLU42 (Zamioudis et al, 2014) and rice Os1bglu4 (Rouyi et al, 2014), in senescence comes from the early onset of glucosidase activity in the B73 compared with PHG35. The b-glucosidase activity also increases during Arabidopsis leaf senescence (Patro et al, 2014), although the exact role of this process remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…From those that contain the WOX binding site and were downregulated in both GCN5 RNAi and wox11 mutant, we selected eight genes from representative categories (including metabolism, cell component, and hormone) for experimental validation. These genes included auxin transport-related OsPIN9, cell wall biosynthesis-related CESA9 (encoding cellulose synthase), CSLF6 (cellulose synthase-like; Jin et al, 2015), and OsEXPA23 (expansin precursor), and energy metabolism-related OsGLU5 (1,4 b-endoglucanase; Zhang et al, 2012), Os1bglu5 (b-glucosidase), Os9bglu33 (b-glucosidase; Rouyi et al, 2014), and OsALDO (fructose-bisphosphate aldolase, a key enzyme of glycolysis). qRT-PCR analysis indicated that all of these genes were indeed downregulated in crown roots of GCN5 and ADA2 RNAi and wox11 mutant plants compared with the respective wild type (Figures 6A to 6C).…”
Section: Gcn5 Rnai Preferentially Reduces the Expression Of Rootspecimentioning
confidence: 99%
“…This process of glycosylation and deglycosylation offers an efficient mechanism that regulates the homeostasis of secondary metabolites and is not limited to plants only but extends to other domains of life like archaea, eubacteria, and animals. Furthermore, the subcellular localization, substrate specificity, and conditions under which ␤-glucosidases come into contact with their physiological substrates determine their biological role (10) and remain an area of intensive study. It is, therefore, important to deepen our knowledge on how plants regulate the individual members of ␤-glucosidases in response to developmental and environmental cues and how the released metabolites modulate the plant's physiological response.…”
mentioning
confidence: 99%